Evaluation of the Expression of the Inhibitor of Apoptosis Protein Family and Human Telomerase Reverse Transcriptase in Patients With Advanced Colorectal Adenoma - Choi, Joon Young; Yoon, Hyuk; Choi, Yoon Jin; Shin, Cheol Min; Park, Young Soo; Kim, Nayoung; Lee, Dong Ho (Journal of cancer prevention, 2017)
It has been reported that the expression of the inhibitor of apoptosis protein (IAP) family increases in patients with colon cancer. We evaluated the expression of the IAP family and human telomerase reverse transcriptase (hTERT) in normal colon mucosa from patients with advanced colorectal adenoma and investigated their features according to characteristics of advanced colorectal adenoma. While resections of polyps were performed in patients (n = 80) diagnosed with advanced colorectal adenoma or carcinoma in situ, additional normal tissues were obtained from the sigmoid colon. In healthy patients (n = 16), blind biopsies were performed on the sigmoid colon. The expression of the IAP family, including survivin, XIAP, cIAP1, and cIAP2, and hTERT, were analyzed by real-time PCR in both groups. A total of 80 advanced colorectal adenoma patients (71.3% male, mean age of 60.4 years) and 16 control patients were enrolled in this study. The mean ranking of cIAP2 was higher in the control group (68.88 vs. 44.43, = 0.001). The expression levels of hTERT, survivin, XIAP, and cIAP from both groups showed no differences. The expression of survivin, XIAP, cIAP1, cIAP2, and hTERT depending on certain factors of advanced adenoma, including the number (two or fewer vs. three or more), size (smaller than 1 cm vs. larger than 1 cm), grade of dysplasia (low grade adenoma vs. high grade adenoma), pathology (tubular adenoma vs. villous adenoma), and presence of endometrial intraepithelial neoplasms, showed no significant correlations in the Mann-Whitney U-test. The expression of the IAP family and hTERT, except cIAP2, in the normal mucosa of patients with advanced colorectal adenoma were not different from those of the control group. There were no differences in the IAP family and hTERT according to the characteristics of advanced adenoma.